Odoo-Based ERP System Design At Distribution Company - Rama Julian Dwi Andika; Sophia Fadhila Albany Tanjung (JTI: Jurnal Teknik Industri, 2025)
PT XYZ is a distribution company engaged in the sale of consumer products. Business processes in warehouse management are still carried out manually, resulting in various obstacles such as delays in stock recording, the risk of human error, and difficulties in tracking goods. This study aims to analyze system requirements and design a digital solution through the implementation of the Inventory module in Odoo ERP. The methods used include direct observation, interviews with related parties, and document analysis to understand the ongoing business processes and identify key problems. The results show that the existing system does not support real-time stock management automation, recording of goods receipts and expenditures, and effective reporting. The proposed solution is the design of an Odoo-based information system that includes the functions of goods receipt, goods expenditure, and stock mutation tracking with an easy-to-use interface integration. This document presents use case diagrams, activity diagrams, and a system requirements analysis as the basis for development. The conclusion of this study is that the implementation of Odoo Inventory can help improve warehouse operational efficiency, reduce recording errors, and provide accurate and up-to-date stock data to support managerial decision-making. Keywords: Warehouse Management, Information Systems, Odoo ERP, Inventory Management, System Requirements Analysis.